Mitochondrial DNA deletions detected by Multiplex Ligation-dependent Probe Amplification - Mayorga, Lía (2015)
The genetic diagnosis algorithm for mitochondrial (mt) diseases starts looking for deletions and common mutations in mtDNA. MtDNA's special features, such as large and variable genome copies, heteroplasmy, polymorphisms, and its duplication in the nuclear genome as pseudogenes (NUMTs), make it vulnerable to diagnostic misleading interpretations. Multiplex Ligation-dependent Probe Amplification (MLPA) is used to detect copy number variations in nuclear genes and its application on mtDNA has not been widely spread. We report three Kearns Sayre Syndrome patients and one Chronic Progressive External Ophthalmoplegia adult,whose diagnostic mtDNA deletions were detected by MLPA using a very low amount of DNA. This managed to dilute the NUMT interference as well as enhance MLPAs efficiency. By this report, we conclude that when MLPA is performed upon a reduced amount of DNA, it can detect effectively mtDNA deletions. We propose MLPA as a possible first step method in the diagnosis of mt diseases.